2022
DOI: 10.1007/s11837-022-05209-z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Resistance in 1200°C Steam of a FeCrAl Alloy Fabricated by Three Metallurgical Processes

Abstract: FeCrAl alloys are a leading candidate material for accident tolerant fuel cladding due to their good performance in both normal light-water reactor operating conditions as well as their resilience to high-temperature accident scenarios. For commercial-scale production, new fabrication techniques need to be investigated. In this study, the effects of fabrication methods on the high-temperature steam oxidation performance of C26M (Fe12Cr6Al2Mo in wt.%) were investigated. Three variants of C26M were manufactured:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…A subtle difference can be observed through the fact that the amount of alumina for a given Al content is marginally higher than the amount of chromia for the same Cr content. This is likely a consequence of the greater thermodynamic stability of the alumina [ 12 ]. When sufficient quantities of different metals are present, the probabilities of formation for the various oxides are mapped corresponding to the respective stabilities of the individual oxides; hence, alumina, being more thermodynamically stable at high temperatures, forms in a relatively greater fraction than other oxides [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A subtle difference can be observed through the fact that the amount of alumina for a given Al content is marginally higher than the amount of chromia for the same Cr content. This is likely a consequence of the greater thermodynamic stability of the alumina [ 12 ]. When sufficient quantities of different metals are present, the probabilities of formation for the various oxides are mapped corresponding to the respective stabilities of the individual oxides; hence, alumina, being more thermodynamically stable at high temperatures, forms in a relatively greater fraction than other oxides [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…A consistent effort has been put into improving the oxidation resistance of Ni-based superalloys by adding Al and Cr in the past [ 9 , 10 ]. Fe-based alloys are well studied in terms of oxidation resistance, with FeCrAl being one of the top candidates for both high- and low-temperature oxidation-resistant material [ 11 , 12 ]. At high temperatures (>1000 °C), a thin α-Al 2 O 3 acts as a diffusion barrier between oxide and bulk metal, protecting the oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it seemed logical to explore the possibility of using AM in the production of fuel rod components in LWRs. Hoffman et al 12 and Umretiya et al 19 reported results on exposure of AM Fe12Cr6Al2Mo (C26M) alloys to steam for 2 h at 1200°C 12 . The mass gain of the additively manufactured (AM) C26M coupon was slightly higher than for the wrought and powder metallurgy made coupons.…”
Section: Introductionmentioning
confidence: 99%
“…One of the leading candidates is FeCrAl alloy. FeCrAl alloys have good oxidation resistant at high temperatures exposure 2 . However, its durability at normal operating conditions needs further investigations.…”
Section: Introductionmentioning
confidence: 99%
“…To do so, a systematic and fast approach is necessary. Large number of experiments have been performed primarily at GE 2 and Oak Ridge National Laboratory 3 to understand the oxidation behavior of FeCrAl alloys in air, steam, and simulated Boiling Water Reactor (BWR) at both Normal Water Chemistry (NWC) and Hydrogen Water Chemistry (HWC). Finding optimal composition of alloys through experiments with specific targeted property needs intensive resources and is time consuming as well.…”
Section: Introductionmentioning
confidence: 99%